The Correlation Between Stress Level and the Menstrual Cycle on the Tenth Grade Female Adolescents at SMAN 1 Palangka Raya - Deka Hariyanti; Eva Prilelli Baringbing; Stefanicia Stefanicia (Universitas Ibn Khaldun Bogor, 2026)
Menstruation is a biological process that occurs periodically in females and can be influenced by various factors, one of which is stress level. Adolescence is a period that is vulnerable to stress due to academic, social, and emotional pressures. Prolonged stress can disrupt hormonal balance, especially hormones that regulate the menstrual cycle, such as estrogen and progesterone, potentially causing irregular menstrual cycles.Objective: To determine the correlation between stress level and the menstrual cycle on the tenth-grade female adolescents at SMA Negeri 1 Palangka Raya.Method: This research used a quantitative method with a Cross-Sectional approach. The population consisted of all tenth-grade female students at SMA Negeri 1 Palangka Raya, totaling 280 individuals. A sample of 74 respondents was selected using Accidental Sampling. The instruments used were the Depression Anxiety Stress Scales (DASS 42) to measure stress levels and a menstrual cycle questionnaire to assess menstrual regularity. Data were analyzed using the Chi-Square test. Results: The results showed that most respondents experienced mild to moderate stress levels, and the majority had irregular menstrual cycles. Statistical analysis showed a p-value= 0.00 < 0.05, indicating a significant correlation between stress level and menstrual cycles.Conclusion: There was a significant correlation between stress level and menstrual cycles in fremale adulescent. The support from schools and families was needed to help adolescents manage stress and maintain reproductive health. Future researchers were encouraged to investigate other factors that may affect the menstrual cycle.